2017
DOI: 10.1093/nar/gkx843
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated gene knockout is insensitive to target copy number but is dependent on guide RNA potency and Cas9/sgRNA threshold expression level

Abstract: CRISPR/Cas9 is a powerful gene editing tool for gene knockout studies and functional genomic screens. Successful implementation of CRISPR often requires Cas9 to elicit efficient target knockout in a population of cells. In this study, we investigated the role of several key factors, including variation in target copy number, inherent potency of sgRNA guides, and expression level of Cas9 and sgRNA, in determining CRISPR knockout efficiency. Using isogenic, clonal cell lines with variable copy numbers of an EGFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
(71 reference statements)
6
41
0
1
Order By: Relevance
“…Incorporation of the highly efficient target site of murine Tet2 yielded an average cleavage rate of 89.44% ( n = 16, SD: ±2.64%), thus assuring the reproducibility and cross-experiment comparability of these assays. This result is in line with recent findings that CRISPR–Cas9 efficacy is independent from target site copy number variations ( 39 ).…”
Section: Resultssupporting
confidence: 92%
“…Incorporation of the highly efficient target site of murine Tet2 yielded an average cleavage rate of 89.44% ( n = 16, SD: ±2.64%), thus assuring the reproducibility and cross-experiment comparability of these assays. This result is in line with recent findings that CRISPR–Cas9 efficacy is independent from target site copy number variations ( 39 ).…”
Section: Resultssupporting
confidence: 92%
“…We observed that once KRAB-dCas9 expression is high enough, CRISPRi efficiency depended on the sgRNA expression level. This observation corroborated the previous findings in CRISPR system, that the nuclear concentration of the guide RNA is the limiting factor for efficient DNA targeting (Yuen et al 2017;Ma et al 2016), indicating that the dynamics of ribonucleoprotein formation and DNA targeting is probably similar between CRISPR and CRISPRi procedure. To improve the knockdown efficiency, it is critical to increasing the expression level of sgRNA, and a change of promotor could achieve this goal.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in the CRISPRedited tRNA reads in the first 4-8 days of the iCas9 induction is followed by an increase of the intact tRNA reads on the expense of the CRISPR-edited tRNA reads ( Fig S2). Together, the observed dynamics suggest that most CRISPR editing occurs in the first four to eight days (Yuen et al 2017), and it is then followed by a competition between cells with various types and extents of editing. The cell competition results in a decline in the edited form of the CRISPR-targeted tRNAs that reflects selection against edited tRNA cells.…”
Section: Genomic Editing Of Proliferation Trnas Results In Negative Smentioning
confidence: 87%
“…We chose to explore the relative fitness of the tRNA knockouts based on relative frequency of their targeting sgRNAs at day 7 (relative to day 0), due to the dynamics of the cell population composition along the iCas9 induction. In the early days of the induction, the iCas9 activity does not reach saturation (Yuen et al 2017), thus the cell population is dominated by partially CRISPR-edited cells. In the late days of the iCas9 induction, the less fit CRISPR-targeted tRNA cells might be eliminated from the population due to a negative selection, a process that can result in lower frequency of the tRNA-edited cells.…”
Section: Evaluating the Trna Expression Levels And The Editing Gene Vmentioning
confidence: 99%